The Use of Code Mixing In The Scripts of Berita Ranah Minang TVRI Sumatera Barat Since January Until December 2018 - Delima Febria Trinila; Mac Aditiawarman (Fakultas Sastra Universitas Ekasakti, 2019)
This research is about of code mixing at Television News Program TVRI Sumatera Barat. The research problems are (1) What types of Code Mixing is used in the scripts of Berita Ranah Minang. (2) What are the reason of using code mixing and (3) What does language matrix as language in code mixing. The objective of this study are finding out the levels of code mixing and to explain the factor of using code mixing in scripts of Berita Ranah Minang. The research uses descriptive and qualitative research. Technique of collecting data are (1) reading whole scripts since January until December, (2) collecting the data, the data are purposive data in the forms of word, phrase, idiom and baster, (3) classifying into five levels of code mixing, (4) reducing the data which has been selected based on the theory, it involves the process of selecting and focusing the raw data into refined data. The researcher uses content analysis which focuses on analyzing levels and factors of code mixing in script Berita Ranah Minang. This research finds five levels of code mixing in script. Those are word level, phrase level, baster level and idiom level. The dominant level of code mixing is word level. The research also finds factors of code mixing. Those are code usage limitation, popular term, domicile and time of conversation, conversation topic, function and aim. Code mixing happens because of the characters have some characterization influences code mixing. The character that has prestigious, high level life style, modern characterization produce code mixing in a level phrase.